IMPLEMENTASI METODE WEBQUAL 4.0 DAN IMPORTANCE PERFORMANCE ANALYSIS (IPA) DALAM PENGUKURAN KUALITAS LEADS UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAKARTA BERDASARKAN PENILAIAN PENGGUNA - Muhammad Ramadhan (2022)
The role of technology in the education sector has a positive impact on its fairly rapid and rapid development in carrying out the interests of improving maximum quality and service, UPN Veteran Jakarta provides answers in the form of technology implementation in order to achieve a role in the use of technology. One form of implementation is the presence of a learning system or Learning Management System called Learning Activities Through Digital System or LeADS. The need for user assessment of the quality of LeADS since its presence almost a year is the background of this research. The analysis of this research uses the webqual 4.0 method and Importance Performance Analysis with respondents, namely lecturers and students, then data collection by purposive random sampling to all users. The results of the analysis in this study produced several analyzes, namely validity test, reliability test, gap value analysis, webqual index analysis, and Importance Performance Analysis. Users as respondents judge based on current actual conditions and user expectations assessments, the final results of the research will be given recommendations for display improvements.